2021
DOI: 10.1002/smll.202102146
|View full text |Cite
|
Sign up to set email alerts
|

Defect Etching of Phase‐Transition‐Assisted CVD‐Grown 2H‐MoTe2

Abstract: 2D molybdenum ditelluride (MoTe2) with polymorphism is a promising candidate to developing phase‐change memory, high‐performance transistors and spintronic devices. The phase‐transition‐assisted chemical vapor deposition (CVD) process has been used to prepare large‐scale 2H‐MoTe2 with large grain size and low density of grain boundary. However, because of the lack of precise control of the growth condition, some defects including the amorphous regions and grain boundaries in 2H‐MoTe2 are hardly avoidable. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…CVD growth of 2D TMDCs, such as MoS 2 , [600][601][602][603] MoSe 2 , [604][605][606][607] MoTe 2 , [608][609][610] and WS 2 , [611][612][613][614][615] has also been extensively reported previously. The typical CVD procedure for growing 2D TMDCs involves the direct reaction of chalcogen vapor with transition metal films or precursors.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…CVD growth of 2D TMDCs, such as MoS 2 , [600][601][602][603] MoSe 2 , [604][605][606][607] MoTe 2 , [608][609][610] and WS 2 , [611][612][613][614][615] has also been extensively reported previously. The typical CVD procedure for growing 2D TMDCs involves the direct reaction of chalcogen vapor with transition metal films or precursors.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…In addition to 2D WTe 2 and MoTe 2 , many other 2D transition metal tellurides can be grown via CVD methods. Li et al reported a method that can precisely control 2H-MoTe defects grown by a large-scale phase-change-assisted CVD process using selective etching of I 3 − solutions ( Zhou et al, 2021 ). Liu et al reported a facile CVD method to synthesize Mo x W 1-x Te 2 with controlled thickness and chemical composition ratios to investigate its design of material devices from a topological quantum state perspective ( Chubilleau et al, 2011 ).…”
Section: Preparationmentioning
confidence: 99%
“…On this basis, we provide a comprehensive overview of tellurides in this study, as shown in Figure 1 . We first focus on the preparation methods of telluride electrode materials, including chemical vapor deposition (CVD) ( Wood et al, 2014 ; Zhou et al, 2017b ; Tang et al, 2019 ; Hao et al, 2021 ; Zhang et al, 2021 ; Zhou et al, 2021 ), hydrothermal method ( Wang et al, 2012 ; Hou et al, 2013 ; Oh et al, 2020 ; Qi et al, 2021 ), and electrodeposition ( Morris and Vanderveen, 1993 ; Yu et al, 2018 ), and their electrochemical properties and applications. Subsequently, conceivable perspectives on the challenges and opportunities of 2D telluride electrode materials are proposed to provide insights into future research.…”
Section: Introductionmentioning
confidence: 99%
“…73 The number of people interested in using 2D hetero-phase homojunction has increased in recent years. [74][75][76][77][78] This is because high-performance field-effect transistors necessitate a clean interface as well as a low contact resistance. The channel in these junctions is made of a semiconducting phase called 2H, and the electrodes are made of either a semi-metallic phase called 1T 0 or a metallic phase called 1T.…”
Section: Introductionmentioning
confidence: 99%